Iowa Bird Life, Iowa Ornithologist's Union - Stone, Tomet al (1978)
Field report title "Iowa Bird Life, Iowa Ornithologist's Union" submitted by Tom Stone. Sightings were made at George Wyth Memorial State Park, Sweet Marsh, Union Grove State Park, and Cardinal March State Wildlife Area. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring, 1978. Epson - sheet feed/flatbed